2018
DOI: 10.1111/vcp.12636
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the utility of lymph node fine‐needle aspiration cytology for the staging of malignant solid tumors in dogs

Abstract: 23Background: Fine needle aspiration cytology (FNAC) of lymph nodes (LNs) is routinely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 40 publications
(114 reference statements)
3
51
0
Order By: Relevance
“…11 Sensitivity of lymph node cytology ranged from 63% to 75% in detecting lymph node metastasis of melanomas, sarcomas and mast cell tumours when compared to extirpated lymph nodes in a recent study. 11 For virtually all malignant solid tumours, the metastatic status of the lymph node is one of the most important prognostic indicators of poor survival and governs therapeutic options. 12 The detection of sentinel lymph nodes in veterinary medicine has previously been described with the use of various imaging modalities including contrast radiographic studies, lymphoscintigraphy, contrast-enhanced ultrasonography and with the use of indirect CT lymphography.…”
Section: Introductionmentioning
confidence: 98%
“…11 Sensitivity of lymph node cytology ranged from 63% to 75% in detecting lymph node metastasis of melanomas, sarcomas and mast cell tumours when compared to extirpated lymph nodes in a recent study. 11 For virtually all malignant solid tumours, the metastatic status of the lymph node is one of the most important prognostic indicators of poor survival and governs therapeutic options. 12 The detection of sentinel lymph nodes in veterinary medicine has previously been described with the use of various imaging modalities including contrast radiographic studies, lymphoscintigraphy, contrast-enhanced ultrasonography and with the use of indirect CT lymphography.…”
Section: Introductionmentioning
confidence: 98%
“…Ultrasound or CT guidance may aid in the cytologic sampling of the less accessible retropharyngeal and parotid lymph nodes (RLN and PLN, respectively), depending on operator experience and comfort ( 10 ). Conversely, several veterinary oncologic studies have shown that cytology alone also lacks sensitivity and specificity in the evaluation of potential metastasis to regional lymph nodes ( 3 , 16 , 17 ). Thus, histopathologic evaluation of the draining regional lymph nodes at risk for metastasis remains the gold standard diagnostic staging tool for dogs with oral tumors ( 3 , 8 , 10 , 11 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 With a reported 75% sensitivity of fine-needle aspiration cytology (FNAC) to detect MCT nodal metastasis, LN extirpation has also been recommended to complete MCT staging. 12,13 Lymphadenectomy is an invasive procedure that often necessitates additional surgical preparation and time, extending time under anaesthesia for dogs and costs for owners. It is therefore sometimes difficult to justify when the LN draining status is uncertain and/or when the LN is particularly difficult to remove.…”
mentioning
confidence: 99%